A stable metal cluster-metalloporphyrin MOF with high capacity for cationic dye removal - Wang, Zheng; Zhang, Jian-Hua; Jiang, Ji-Jun; Wang, Hai-Ping; Wei, Zhang-Wen; Zhu, Xunjin; Pan, Mei; Su, Cheng-Yong (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
A metalloporphyrin Cu 5 -cluster based MOF (metal–organic framework), [Cu 4.5 ((H 4 TZPP)(TZPP)Cl 2 )(H 2 O) 0.5 ]·CH 3 NH 2 CH 3 ·7EtOH·8H 2 O (LIFM-WZ-3) was synthesized from the tetrapodal ligand 5,10,15,20-tetrakis[4-(2,3,4,5-tetrazolyl)phenyl]porphyrin (H 6 TZPP) and copper chloride. LIFM-WZ-3 exhibits a rare 2D + 3D → 3D interpenetration topology, of which the frl-type 3D MOF and a layered 2D HOF (hydrogen bond organic framework) are intertwined, leading to an anionic framework with 1D spindle-like channels. Powder X-ray diffraction analysis reveals that the framework is stable in acid, base and various organic solvent environments. LIFM-WZ-3 exhibits moderately high separation performances for CO 2 /CH 4 , CO 2 /N 2 , C 3 H 6 /CH 4 , C 2 H 6 /CH 4 , and C 2 H 4 /CH 4 at room temperature. Specifically, the anionic framework in LIFM-WZ-3 containing dimethylamine cations can selectively adsorb cationic organic dyes from aqueous pollutants for recycle purpose. The high adsorption capacity for methylene-blue (MB + , 983 mg g −1 ) and crystal violet (CV + , 713.5 mg g −1 ) ranks the highest among those MOFs ever reported.